2022
DOI: 10.3390/cancers15010101
|View full text |Cite
|
Sign up to set email alerts
|

CRAC and SK Channels: Their Molecular Mechanisms Associated with Cancer Cell Development

Abstract: Cancer represents a major health burden worldwide. Several molecular targets have been discovered alongside treatments with positive clinical outcomes. However, the reoccurrence of cancer due to therapy resistance remains the primary cause of mortality. Endeavors in pinpointing new markers as molecular targets in cancer therapy are highly desired. The significance of the co-regulation of Ca2+-permeating and Ca2+-regulated ion channels in cancer cell development, proliferation, and migration make them promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 393 publications
0
6
0
Order By: Relevance
“…Tumour development, aggressiveness and poor prognosis of a wide variety of cancers is often also associated with an altered expression of STIM1 and STIM2, as described in detail in Tiffner et al (2022). For example, gastric and colorectal cancer tissues exhibit increased STIM1 expression in comparison with the respective non-cancerous tissues, which apparently promotes invasion and metastasis (Wang et al, 2015;Wen et al, 2016;Xia et al, 2016;Xu et al, 2016).…”
Section: Diseases Associated With Stim Isoforms or Dysregulationmentioning
confidence: 99%
“…Tumour development, aggressiveness and poor prognosis of a wide variety of cancers is often also associated with an altered expression of STIM1 and STIM2, as described in detail in Tiffner et al (2022). For example, gastric and colorectal cancer tissues exhibit increased STIM1 expression in comparison with the respective non-cancerous tissues, which apparently promotes invasion and metastasis (Wang et al, 2015;Wen et al, 2016;Xia et al, 2016;Xu et al, 2016).…”
Section: Diseases Associated With Stim Isoforms or Dysregulationmentioning
confidence: 99%
“…Here, it engages with and activates Orai channels, precipitating Ca 2+ influx or SOCE 1,7,8,[11][12][13] . The implications of STIM1/Orai1 complex malfunctions are profound, implicated in a spectrum of diseases from severe combined immunodeficiency (SCID) to various muscular disorders and inflammatory conditions 1,[14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the CRAC channels’ role in many immune cell functions, they are also potential drug targets for the treatment of various inflammatory reactions, allergic diseases [ 118 , 119 ], and many cancer types [ 20 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ]. Several studies have confirmed that the genetic deletion or inhibition of CRAC channels hinders T cell and mast cell functions and diminishes inflammation of autoimmunity, transplant rejection, and asthma [ 119 ].…”
Section: Introduction—the Role Of Ca 2+ Release-ac...mentioning
confidence: 99%